Diastolic function and functional capacity after a single session of continuous positive airway pressure in patients with compensated heart failure - Bussoni, Marjory Fernanda [UNESP]; Guirado, Gabriel Negretti [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Roscani, Meliza Goi [UNESP]; Polegato, Bertha Furlan [UNESP]; Minamoto, Suzana Erico Tanni [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Universidade de São Paulo (USP), Hospital das Clínicas, 2014)
OBJECTIVE: The effects of acute continuous positive airway pressure therapy on left ventricular diastolic function and functional capacity in patients with compensated systolic heart failure remain unclear.METHODS: This randomized, double-blind, placebo-controlled clinical trial included 43 patients with heart failure and a left ventricular ejection fraction <0.50 who were in functional classes I-III according to the New York Heart Association criteria. Twenty-three patients were assigned to continuous positive airway pressure therapy (10 cmH(2)O), while 20 patients received placebo with null pressure for 30 minutes. All patients underwent a 6-minute walk test (6MWT) and Doppler echocardiography before and immediately after intervention. Clinicaltrials.gov: NCT01088854.RESULTS: The groups had similar clinical and echocardiographic baseline variables. Variation in the diastolic function index (e') after intervention was associated with differences in the distance walked in both groups. However, in the continuous positive airway pressure group, this difference was greater (continuous positive airway pressure group: Delta 6MWT=9.44+16.05x Delta e', p=0.002; sham group: Delta 6MWT=7.49+5.38x Delta e'; p=0.015). There was a statistically significant interaction between e ' index variation and continuous positive airway pressure for the improvement of functional capacity (p=0.020).CONCLUSIONS: Continuous positive airway pressure does not acurately change the echocardiographic indexes of left ventricle systolic or diastolic function in patients with compensated systolic heart failure. However, 30-minute continuous positive airway pressure therapy appears to have an effect on left ventricular diastolic function by increasing functional capacity.
Keywords: Six-Minute Walk Test; Echocardiogram; Left Ventricle; Systolic Heart Failure; Exercise Tolerance